2011
DOI: 10.1021/cm200753g
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tavorite-Structured Cathode Materials for Lithium-Ion Batteries Using High-Throughput Computing

Abstract: ABSTRACT. Cathode materials with structure similar to the mineral tavorite have shown promise for use in lithium-ion batteries, but this class of materials is relatively unexplored. We use high-throughput density-functional-theory calculations to evaluate tavorite-structured oxyphosphates, fluorophosphates, oxysulfates, and fluorosulfates for use as cathode materials in lithium-ion batteries. For each material we consider the insertion of both one and two lithium ions per redox-active metal, calculating averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
243
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(263 citation statements)
references
References 62 publications
15
243
1
4
Order By: Relevance
“…The theoretically predicted Li ion intercalation potentials have been found to be in excellent agreement with the experiments, which shows that the material design using prior ab initio methods is a powerful tool [151]. In recent years, high-throughput computing approaches for materials design are gaining rapid attention, in particular the Li ion battery materials, and this method has been applied to screen a large number of battery materials by applying DFT+U ab initio methods [155,156].…”
Section: Redox Potentials Of LI Ion Battery Materials Semiconductorsmentioning
confidence: 61%
“…The theoretically predicted Li ion intercalation potentials have been found to be in excellent agreement with the experiments, which shows that the material design using prior ab initio methods is a powerful tool [151]. In recent years, high-throughput computing approaches for materials design are gaining rapid attention, in particular the Li ion battery materials, and this method has been applied to screen a large number of battery materials by applying DFT+U ab initio methods [155,156].…”
Section: Redox Potentials Of LI Ion Battery Materials Semiconductorsmentioning
confidence: 61%
“…[1][2][3][4][5][6][7][8] Reaction energies are also critical to the ab initio study of the thermodynamic stability of known materials [9][10][11][12][13][14] or the prediction of novel phases. [15][16][17][18][19][20][21][22][23][24][25][26][27] Indeed, it is a compound's energy relative to the energy from combinations of other phases, which determines its stability.…”
Section: Introductionmentioning
confidence: 99%
“…These phase diagrams are useful when studying the phase stability of known but also predicted compounds. Several recent studies relied on such phase diagrams to investigate the stability of new proposed phosphates-based compounds for lithium-ion batteries, [20][21][22] new predicted ternary oxides, 18 new iron borides 17 or new intermetallics. 16,26 Zero K phase diagrams based on GGA computations for all compounds in the ICSD are also available online through the Materials Project.…”
mentioning
confidence: 99%
“…67,68 Another class of phosphate cathodes that has enjoyed considerable interest is the tavorite family, with a structure similar to that of LiFe (PO 4 )(OH). [69][70][71][72][73] Mueller et al 74 performed a comprehensive evaluation of tavorites as potential intercalation cathodes for Li-ion battery chemistry. In terms of diffusivity, they found that VOPO 4 , VOPO 4 F and FeOPO 4 have reasonably low activation energies (200-500 meV) for Li migration in 1D but much higher activation energies in 2D and 3D (4700 meV).…”
Section: Polyanion Oxidesmentioning
confidence: 99%